Comparison of forward and backward gait in males with and without intellectual disabilities - Gimunová, M; Bozděch, M; Skotáková, A; Grün, V; Válková, H (Journal of intellectual disability research, 2021)
BACKGROUND: Intellectual disabilities (ID) affect both cognitive and motor functions. The backward gait is a daily activity and its assessment is used for fall risk estimation and training in the general population. For proper use of backward gait as a rehabilitation tool and in fall prevention programmes for people with ID, it is necessary to determine the backward gait characteristics in the ID population. The aim of this study was to compare the differences between forward and backward gait in persons with nonsyndromic mild and moderate ID, persons with Down syndrome (DS) and a control group of healthy adults. METHODS: Fifty males divided into four groups (mild ID: n = 15, moderate ID: n = 19, DS: n = 6, controls: n = 10) participated in this study. All participants were asked to walk both forward and backward, barefooted and at their natural velocity on a Zebris FDM platform. The Kruskal-Wallis H test was used to compare differences between the analysed groups in forward and backward gait. The Mann-Whitney U test was used to compare the differences between forward and backward gait within each group. RESULTS: The velocity was significantly slower in moderate ID and DS compared to controls in forward and backward gait. When comparing forward and backward gait within each group, the gait velocity decreased in backward gait compared with forward gait by 21.80% in controls, by 33.89% in mild ID, by 34.45% in moderate ID, and by 40.32% in DS. In both moderate ID and DS, the mean backward velocity was slower than 2.16 km/h, the velocity used to identify elderly fallers in the general population. CONCLUSIONS: Gait velocity was especially affected in DS and moderate ID compared with controls. In both mentioned groups, the backward gait velocity suggests an increased risk of falling. Future studies are necessary to examine the possibility of improving balance control and leg muscle strength by backward walking training in the ID population.
Keywords: Down syndrome; svalová síla; Humans; Postural Balance; Aged; dospělí; chůze (způsob); senioři; lidé; Accidental Falls; mentální retardace; Gait; Muscle Strength; chůze; Adult; Intellectual Disability; Male; úrazy pádem; Special Olympics; intellectual disability; Walking; forward gait; backward gait; mužské pohlaví; posturální rovnováha